Anomalous Behavior of Hc3/Hc2 near Tc for Sn-In and In-Bi Alloy Systems - Maloney, M.D.; de la Cruz, F.; Cardona, M. (American Physical Society, 1970)
Fil: de la Cruz, F. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Brown University; Estados Unidos